Developmental origins of brain disorders: roles for dopamine - Money, Kelli M.; Stanwood, Gregg D. (Frontiers in Cellular Neuroscience, 2013)
Neurotransmitters and neuromodulators, such as dopamine, participate in a wide range of behavioral and cognitive functions in the adult brain, including movement, cognition, and reward. Dopamine-mediated signaling plays a fundamental neurodevelopmental role in forebrain differentiation and circuit formation. These developmental effects, such as modulation of neuronal migration and dendritic growth, occur before synaptogenesis and demonstrate novel roles for dopaminergic signaling beyond neuromodulation at the synapse. Pharmacologic and genetic disruptions demonstrate that these effects are brain region- and receptor subtype-specific. For example, the striatum and frontal cortex exhibit abnormal neuronal structure and function following prenatal disruption of dopamine receptor signaling. Alterations in these processes are implicated in the pathophysiology of neuropsychiatric disorders, and emerging studies of neurodevelopmental disruptions may shed light on the pathophysiology of abnormal neuronal circuitry in neuropsychiatric disorders.